Green Deal for Europe: More Climate Protection and Fewer Fossil Fuel Wars - Claudia Kemfert (Intereconomics, 2019)
A Green Deal for Europe can set standards for ambitious climate protection, for an investment programme in future markets and for strengthening the European economy and European and non-European security. Climate protection and a sustainable energy transition not only create economic opportunities but also reduce geopolitical disputes, thus securing peace within and outside Europe. In order to meet the emission reduction targets of the Paris climate agreement and the EU deal, the share of renewable energy sources would have to increase significantly faster.
Keywords: 330